Central Asian intellectuals on Islam: between scholarship, politics and identity - Roche, Sophie; Wilkowsky, Dina; Féaux de la Croix, Jeanne (Studien, 2014)
This book brings together a selection of academic texts on Islam in Central Asia and the biographies of the authors, most of them trained in Oriental Studies (vostokovedinie). The collection of biographies of Islamic intellectuals, ranging from officeholder to (opposition) politicians and academics, covers the late socialist period, perestroika and independence. They document the long-term transformations of Islamic identities of Central Asians and the impact intellectuals have on shaping contemporary society.